Study on the Optimal Construction Time of Adjacent Pile Foundation Considering the Thermal Stability of the Existing Pile Foundation - Xiangyang Shi; Yunxing Wang; Ziqiang Zhou; Long Huang (Buildings)
To control settlement deformation in permafrost regions, new piles are constructed for remediation. However, the construction of new piles inevitably causes thermal disturbance to the existing pile foundations. A three-dimensional quarter-model of a rectangularly arranged pile group was established to analyze temperature field changes under construction time in odd-numbered months. In addition, a refreezing rate formula based on the effective freezing temperature was developed to examine the annual changes. The results indicate that the thermal disturbance from the new pile foundation construction gradually weakens over time but does not subside within a year, which significantly affects 75% of the existing pile length, and that the refreezing rate continues to increase after construction in November, i.e., the initial month of the cold season, and is maximized in approximately 60 days. This result suggests that November is the optimal time for such construction activities. The findings of this study provide valuable insights for pile engineering practices to mitigate issues caused by permafrost degradation.